Sistem Bilangan Veda dari India dalam Perspektif Sejarah dan Ilmiah: Studi Literatur Kritis - Feronika Br Siahaan; Natasya Agustina; Mangaratua Marianus Simanjorang (Pusat Riset dan Inovasi Nasional, 2025)
The Vedic numeral system from India is one of the ancient mathematical heritages with significant historical and scientific value. This study aims to examine the Vedic numeral system from historical and scientific perspectives through a critical literature review. The research method used is a literature study that gathers and analyzes various academic sources regarding the origins, development, and relevance of the Vedic numeral system in modern mathematics. The findings indicate that this system has made significant contributions to the development of the concept of zero and the decimal system, which form the foundation of modern mathematics. Additionally, the principles of Vedic Mathematics have been proven to simplify various arithmetic operations, making it an efficient method for teaching mathematics. Despite its advantages, the application of the Vedic numeral system in education still faces challenges, particularly in academic documentation and adaptation into modern curricula. Therefore, further research is needed to evaluate its effectiveness in learning and its application in various scientific and technological fields.